2004
DOI: 10.1128/iai.72.11.6589-6596.2004
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing: a Transcriptional Regulatory System Involved in the Pathogenicity of Burkholderia mallei

Abstract: Numerous gram-negative bacterial pathogens regulate virulence factor expression by using a cell density mechanism termed quorum sensing (QS). An in silico analysis of the Burkholderia mallei ATCC 23344 genome revealed that it encodes at least two luxI and four luxR homologues. Using mass spectrometry, we showed that wild-type B. mallei produces the signaling molecules N-octanoyl-homoserine lactone and N-decanoyl-homoserine lactone. To determine if QS is involved in the virulence of B. mallei, we generated muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 38 publications
0
73
0
1
Order By: Relevance
“…In the past, Syrian hamsters had been the most effective model to study the pathogenicity of B. mallei when infected intraperitoneally [7,8,9,29]. However, purchasing and handling of Syrian hamsters is costlier than mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, Syrian hamsters had been the most effective model to study the pathogenicity of B. mallei when infected intraperitoneally [7,8,9,29]. However, purchasing and handling of Syrian hamsters is costlier than mice.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia mallei, glanders, sucrose-resistant strain, recombination, ctpA, carboxy-terminal protease, attenuation, efficacy, laboratory animals, mice network [9], and a type VI secretion system [10] are important for the virulence of this bacterium. Molecular characterization of the in vivo survival process (or pathogenicity) of B. mallei is important because it would provide guidance for the development of measures for the prevention and control of glanders.…”
Section: Subject Termsmentioning
confidence: 99%
“…This appears to be the case for the 120-kb R2-I2-containing DNA element. Other investigators have shown that both of the B. mallei quorum-sensing systems contribute to virulence (61). It is logical to assume that system 2 in B. pseudomallei is not critical for virulence.…”
Section: Vol 191 2009mentioning
confidence: 99%
“…pseudomallei-B. thailandensis group because quorum sensing has been implicated in the virulence of B. mallei and B. pseudomallei and because each member of this group has multiple quorumsensing systems (60)(61)(62). Quorum sensing involves production of and response to a self-produced extracellular signal that allows individuals to monitor the group population density (3,21,67).…”
Section: Burkholderia Thailandensis Burkholderia Pseudomallei Andmentioning
confidence: 99%
“…This interaction leads to conformational changes of the regulator and subsequent modifications of target gene transcription. The phenotypes regulated by QS are as diverse as bioluminescence (37), competence (49), biofilm formation (44), and virulence (50,75,78).We identified two LuxR-type regulators in the sequenced B. melitensis genome (16), the previously described VjbR regulator (BMEI1116) (14) and a second regulator, currently undergoing characterization, called BabR (BMEI1758). Despite several attempts, we were not able to identify an AHL synthetase in B. melitensis.…”
mentioning
confidence: 99%